A case of non-alcoholic steatohepatitis solved by unani formulations (Qurs-e-Zarishk, Arq mako and Arq Kasni) - Hussain, Zaffar; Hamid, Shugufta; Wani, Nasir Nazir; Jalal, Barjes; Yaqoob, Farhan (International Journal Of Community Medicine And Public Health, 2025)
Non-alcoholic steatohepatitis is defined as the fat buildup of greater than 5 percent together with the histologic indications of necro-inflammation and hepatocyte ballooning and degeneration. A 60-year-old female patient was diagnosed with Non-alcoholic steatohepatitis on 27/2/2024. She was stable without any symptoms until she developed abdominal discomfort and approached the OPD, department of Moalajat, RRIUM, Srinagar. She was a diagnosed case of NASH, which was confirmed with the help of fibro scan. The regression of NASH, may have been due to anti-inflammatory, hepatoprotective, antioxidant, hypolipidemic, hypoglycemic effects of the drugs given to the patient. In addition to this, the drugs also possess liver strengthening, demulcent and diuretic effects which add more to their healing effects.